CREDIT PORTFOLIO RISK MANAGEMENT: THEORY AND PRACTICE - Затворницький, Костянтин (Socio-economic relations in the digital society, 2019)
The article raises and comprehensively analyses the issue of efficient credit portfolios’ risk management of Ukrainian banks. It has been substantiated that the imperfect strategy and tactics of risk management in banks has led to the emergence of their fi nancial and reputational losses. It has been proven that the high level of nonperforming bank loans of all ownership forms creates obstacles to the banking system development and prevents its advanced reforming. Insufficient coverage and depth of existing bank risk management systems makes it necessary to spend additional resources to support them, distracting them from other goals. The importance of efficient interaction between bank management and personnel as an integral element of feedback necessary for the quality functioning of risk management systems has been emphasized. The role of bank employees’ motivation at all subordination levels in ensuring the improvement of existing systems of bank risk management has been revealed. Theoretical and practical issues of risk management of commercial banks’ credit portfolios with consideration of their formation factors have been considered. The essence of the relationship between the concepts of ‘structure’, ‘quality’ and ‘risk’ has been revealed, a number of risks affecting the formation of a bank loan portfolio have been identified. Legislative aspects of credit activity regulation of Ukrainian banks have been investigated. The assessment of application expediency of risk management new requirements in Ukrainian banks have been presented. The banking system credit risk level of Ukraine has been analyzed and approaches to minimization and elimination of banks’ credit activity risks have been offered. Participants of banks’ reputational risk formation have been classifi ed. The structural elements of an eff ective system of bank risk management have been
Keywords: operational risk; credit risk; interest rate risk; reputational risk; risk assessment; credit portfolio; liquidity; risk management